High risk sexual behaviors are associated with sexual violence among a cohort of women in Durban, South Africa - Gaffoor, Zakir (BioMed Central, 2013)
BACKGROUND: Studies show Gender Based Violence (GBV) to be significantly associated with risky sexual behaviour. In South Africa the incidence of GBV is reportedly high, and there is a strong argument for GBV to be a driver of HIV infection rates. This study describes the prevalence of Forced Sex (FS) experiences of women who enrolled into an HIV biomedical intervention study, and its association with risky sexual behaviour. FINDINGS: In this study, sociodemographic and behavioural data from women enrolled in the Carraguard™ trial, were assessed in relation to FS using logistic regression. The results indicated that 193/1485 (13%) of women reported ever experiencing FS at the screening visit. Women who were 30 years and older; reported having sex for cash; multiple partners; changing partners during the trial; inconsistent condom use during the trial; and 3 or more sex acts in the 2 weeks prior to screening, were significantly more likely to have experienced forced sex. CONCLUSIONS: The results of this study are broadly consistent with those found in other studies and are similar in profile to women at higher risk for HIV acquisition in our setting. This study indicates a need for GBV prevention to be integrated with HIV prevention programmes.